Production of homozygous klotho knockout porcine embryos cloned from genome-edited porcine fibroblasts - Sanghoon Lee; Min Hee Jung; Hyun Ju Oh; Ok Jae Koo; Se Chang Park; Byeong Chun Le (The Korean Society of Animal Reproduction and Biotechnology, 2016)
Even though klotho deficiency in mice exhibits multiple aging-like phenotypes, studies using large animal models such as pigs, which have many similarities to humans, have been limited due to the absence of cell lines or animal models. The objective of this study was to generate homozygous klotho knockout porcine cell lines and cloned embryos. A CRISPR sgRNA specific for the klotho gene was designed and sgRNA (targeting exon 3 of klotho) and Cas9 RNPs were transfected into porcine fibroblasts. The transfected fibroblasts were then used for single cell colony formation and 9 single cell?derived colonies were established. In a T7 endonuclease I mutation assay, 5 colonies (#3, #4, #5, #7 and #9) were confirmed as mutated. These 5 colonies were subsequently analyzed by deep sequencing for determination of homozygous mutated colonies and 4 (#3, #4, #5 and #9) from 5 colonies contained homozygous modifications. Somatic cell nuclear transfer was performed to generate homozygous klotho knockout cloned embryos by using one homozygous mutation colony (#9); the cleavage and blastocyst formation rates were 72.0% and 8.3%, respectively. Two cloned embryos derived from a homozygous klotho knockout cell line (#9) were subjected to deep sequencing and they showed the same mutation pattern as the donor cell line. In conclusion, we produced homozygous klotho knockout porcine embryos cloned from genome-edited porcine fibroblasts.